Analisa Peramalan Permintaan Mobil Daihatsu Dengan Metode Time Series - Fikri Oktiandar; M Rafiqi; Muhammad Akram Ridiya; Nurul fatayat (Jurnal Teknik Mesin Unsyiah, 2020)
In production activities, forecasting is carried out to determine the amount of demand for a product and is the first step of the process of production planning and control. In forecasting, it is determined what type of product is needed (what), the amount (how many), and when it is needed (when). The purpose of forecasting in production activities is to reduce uncertainty so that an estimate is obtained that is close to the actual situation. The process of forecasting the demand for Daihatsu cars is carried out using the moving average method (Moving Average = MA). Then also do the EOQ static model making to determine the economic amount each time the order and the creation of an MRP system as a planning requirement based on time stages.